Evaluation on self-cleaning protective coating using chitosan base for corrosion application - Save, Li Hong (2024)
This research aims to evaluate the effectiveness of a chitosan-based self-cleaning protective coating for corrosion applications through laboratory testing and analysis. The study focuses on assessing the corrosion resistance of the coating under various environmental conditions to determine its optimal application. The results obtained from this research will provide valuable insights into the potential of chitosan-based self-cleaning protective coatings for effective corrosion protection. Corrosion is a significant challenge that affects adversely the performance and lifespan of metallic materials. The development of innovative protective coatings has become in crucial mitigating corrosion-related issues. Self-cleaning protective coatings, particularly those based on chitosan have shown promise in addressing this challenge. Chitosan derived from crustacean shells possesses favourable properties such as biocompatibility biodegradability and corrosion resistance. This research aims to further explore the potential of chitosan-based self-cleaning protective coatings for application corrosion. Laboratory testing conducted is to assess the corrosion resistance of the chitosan-based self-cleaning protective coating by manipulating the concentration of chitosan from 0.1wt% to 0.5wt% while the ratio of SiO2 and ZnO ratio set to be 1:1. The best result in this case where 0.5wt% chitosan-SiO2-ZnO showing the positive effect after the immersion of 3.5wt% of NaCl for 2 weeks. The coating's performance is evaluated through water droplet contact angle tests (GAC), and the results of the laboratory testing reveal the contact angle obtained at 23.1°, 24.6° and 34.9°±2.4, proving the coating has hydrophilic properties. The morphological properties of 0.5wt% chitosan-SiO2-ZnO hybrid particles were studied with scanning electron microscopy (SEM). The EIS was carried out by fitting the semicircles with equivalent circuit. Bode plot to analyze magnitude and phase changes or the mechanism of the coating formulation introduced after the fitting is done. The final obtained circuit is R[L.R][CPE] indicates that it would be a standard Randles circuits in series with inductance that is parallel with resistor of coating and a constant phase element in series with this, where the diffusion characteristics and the signiﬁcant features of the spectra are discussed.